Improving the Dysregulation of FoxO1 Activity Is a Potential Therapy for Alleviating Diabetic Kidney Disease - Wang, Yan; He, Weichun (Frontiers in Pharmacology, 2021)
A substantial proportion of patients with diabetes will develop kidney disease. Diabetic kidney disease (DKD) is one of the most serious complications in diabetic patients and the leading cause of end-stage kidney disease worldwide. Although some mechanisms have been revealed to contribute to the understanding of the pathogenesis of DKD and some drugs currently in use have been shown to be beneficial, prevention and management of DKD remains tricky and challenging. FoxO1 transcriptional factor is a crucial regulator of cellular homeostasis and posttranslational modification is a major mechanism to alter FoxO1 activity. There is increasing evidence that FoxO1 is involved in the regulation of various cellular processes such as stress resistant, autophagy, cell cycle arrest, and apoptosis, thereby playing an important role in the pathogenesis of DKD. Improving the dysregulation of FoxO1 activity by natural compounds, synthetic drugs, or manipulation of gene expression may attenuate renal cells injury and kidney lesion in the cells cultured under a high-glucose environment and in diabetic animal models. The available data imply that FoxO1 may be a potential clinical target for the prevention and treatment of DKD.